42 The use of optical coherence tomography in imaging the airways in children. (4th October 2017) - McLaren, C; Patel, P; Roebuck, D
Abstract : Background: Optical coherence tomography (OCT) uses near infrared light to produce cross-sectional images. OCT can be used to provide high-resolution images of the walls of many anatomical structures such as arteries, veins, the bladder and the airway. These are similar to the images provided by intravascular ultrasound. Methods: We have used OCT to assess cartilage of the airways in children, mainly in the context of suspected long segment congenital tracheal stenosis. This is a retrospective study of all the children in our hospital who underwent OCT between November 2006 and October 2016. Results: We performed 177 OCT procedures in 161 patients (14 patients underwent 2 procedures and 1 patient underwent 3 procedures). The age range was 2 days to 15 years, median 8 months. 91 were boys and 70 were girls. Complete tracheal or bronchial rings were seen in 89 procedures. It was not possible to confirm the presence of complete rings in 15 procedures. Absent cartilage was diagnosed in 5 and in12 procedures we showed dysplastic cartilage. Seven procedures were performed for the assessment of airway stents. Conclusion: OCT provides high quality images of the wall of the airway in children and can be utilised to assess airway cartilage in children with complex airway conditions.